2021
DOI: 10.3390/cells10051170
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Effects of Myeloid-Derived Suppressor Cells in Cancer and Immunotherapy

Abstract: The primary function of myeloid cells is to protect the host from infections. However, during cancer progression or states of chronic inflammation, these cells develop into myeloid-derived suppressor cells (MDSCs) that play a prominent role in suppressing anti-tumor immunity. Overcoming the suppressive effects of MDSCs is a major hurdle in cancer immunotherapy. Therefore, understanding the mechanisms by which MDSCs promote tumor growth is essential for improving current immunotherapies and developing new ones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 191 publications
(233 reference statements)
0
39
0
1
Order By: Relevance
“…through the reaction of .NO and O2-inhibiting the recruitment of tumor specific T cells and leading to tumor progression [111]. Targeting of either the G-MDSC or the Mo-MDSC mechanism did not affect T cell suppression by the other pathway, suggesting that these two mechanisms acted independently to regulate T cell activity (Figure 5A, 5B).…”
Section: Role Of No In the Regulation Of Myeloid Derived Suppressor Cells (Mdscs) In The Tmementioning
confidence: 94%
See 1 more Smart Citation
“…through the reaction of .NO and O2-inhibiting the recruitment of tumor specific T cells and leading to tumor progression [111]. Targeting of either the G-MDSC or the Mo-MDSC mechanism did not affect T cell suppression by the other pathway, suggesting that these two mechanisms acted independently to regulate T cell activity (Figure 5A, 5B).…”
Section: Role Of No In the Regulation Of Myeloid Derived Suppressor Cells (Mdscs) In The Tmementioning
confidence: 94%
“…MDSCs express high levels of indoleamine 2,3-dioxygenase 1 (IDO1) that deplete L-tryptophan and kynurenine production and lead to T cell death. MDSCs also generate nitrogen reactive species (RNS) peroxynitrite through the reaction of .NO and O2-inhibiting the recruitment of tumor specific T cells and leading to tumor progression [111]. Targeting of either the G-MDSC or the Mo-MDSC mechanism did not affect T cell suppression by the other pathway, suggesting that these two mechanisms acted independently to regulate T cell activity (Figure 5A,B).…”
Section: Role Of No In the Regulation Of Myeloid Derived Suppressor Cells (Mdscs) In The Tmementioning
confidence: 99%
“…Tumors express neoantigens that should be able to generate an immune response that recognizes and eradicates cancer cells. There are various mechanisms that suppress anti-tumor immunity [ 33 , 34 , 35 ]. Chronic inflammation is one of the key factors that cause immune suppression [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is one of the key factors that cause immune suppression [ 36 ]. One of the mechanisms through which inflammation leads to immune suppression is by recruitment of CD11b+Gr1+ myeloid derived suppressor cells (MDSC) into the tumor microenvironment [ 33 , 34 ]. CD11b+Gr1+ cells are well known to have a suppressive effect on anti-tumor immune responses [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most of the preclinical models discussed [119,120], it is shown that the inhibitory activity of MDSCs is specifically directed against T responses and probably NK cell responses, although it has generally not been investigated. In fact, the therapeutic effect may be thwarted in T-cell-depleted mice.…”
Section: Immunosuppressive Activity Of Mdscs On T Cell Responsesmentioning
confidence: 99%